The Caesarean Sections Claims of National Health Insurance in the East Java Region Hospital - Mustofa, Tika Rahhmatillah; Meliala, Andreasta (BPJS Kesehatan, 2024)
WHO (2015) sets the standard for sectio caesarea at 10-15%. The proportion of SC deliveries in East Java was 22.4% in 2018, higher than the national average of 17.6%. The burden of JKN financing on childbirth is increasing and is among the top 10 most CBGs cases nationally. As an effort to control quality and control costs, BPJS Health in coordination with the Quality Control Cost Control Team (TKMKB) issued guidelines and self-assessment instruments for cesarean section (SC) in 2020. This study was conducted to explore the picture of SC before and during the implementation of the SC Self-Assessment Instrument in National Health Insurance patients in East Java. Of the 837,809 study subjects, 247,508 (60.5%) had SC delivery. Sectio Caesarea delivery of National Health Insurance patients at FKRTL in East Java is associated with individual factors, namely age and type of JKN membership and service factors, namely SC Self-Assessment Instrument, class of care, severity level, and hospital type. Implementation of the SC Self-Assessment Instrument has not been optimal in reducing the SC rate. A comprehensive strategy is needed to reduce the rate of sectio caesarean delivery, including interventions for pregnant women and families; health workers, health facilities, and professional organizations.